Engineering of Point Defects and Formation Mechanisms of PbTe–CdTe Solid Solutions - Tsymbalyuk, T.P. (Physics and Chemistry of Solid State, 2016)
The crystal-quasichemical formulas were proposed in paper. There were obtain the dominant point defects of Pb1-xCdxТе solid solutions on the base of initial binary solutions PbТе and CdTe of the n- and р-type of conductivity. The dependence of defect concentrations, such as charge carriers and Hall’s concentration due composition of solid solutions were calculated.